The Mechanical and Thermodynamical Theory of Plasticity. - Negahban, Mehrdad (CRC Press, 2012)
""An excellent text for a graduate-level course in plasticity ... the approach and selection of topics are appropriate for the audience. ... Professor Negahban has done an excellent job in presenting a unified approach to include thermal effects in the theory of finite deformation of plastic solids. The simple thermo-mechanical analog presented at the beginning of the chapter is also very instructive to the reader. {presented figures are] particularly helpful in understanding the mechanisms in a simple (one-dimensional) setting ... The learning features included in this chapter are excellent (the fi.